A heat energy recovery system from tunnel waste water. Issue 5 (1st September 2016) - Hytiris, Nicholas; Ninikas, Konstantinos; Emmanuel, Rohinton; Aaen, Bjorn; Younger, Paul L.
Abstract : Minimising the maintenance costs of water ingress in transportation tunnels is a significant challenge. Decreasing the overall cost of a ground source heat pump system is equally challenging. An effort to address both issues at once has been made in relation to groundwater ingress in the Glasgow Subway system. Inflowing water is a valuable resource which could be channelled through a water source heat pump (WSHP) to produce heat energy for domestic or public use (heating and domestic hot water). Water flow and water temperature have been recorded for a year at 21 different points within the network of the underground tunnels and platforms. The points of highest water influx were identified, and the heat energy content of each has been calculated. Working from these data, several options were identified for capturing the water and diverting it to a WSHP to recover heat. A final design for a pilot system within the tunnels was developed. The findings of this study are expected to contribute a renewable heat solution through a cost-effective heat pump system design.